Etiologic and clinical characterization of patients with recurrent spontaneous intracerebral hemorrhage - Wolf, Marc; Alonso, Angelika; Ebert, Anne; Szabo, Kristina; Chatzikonstantinou, Anastasios (European neurology, 2016)
Background: The impact of recurrent stroke has been extensively addressed with regard to ischemic stroke, revealing potentially different etiologies of recurrent events in the individual patient. In contrast, data on recurrent intracerebral hemorrhage (ICH) are scarce, especially considering etiologic characterization. We aimed to determine the etiology of recurrent ICH at each event to identify potential etiologic changes. Patients and Methods: We analyzed the data of patients admitted to our stroke unit with recurrent ICH between 1998 and 2014 with regard to clinical characteristics and etiology. Results: Thirty-three patients (2.6%) with recurrent ICH were identified. Mean age (mean ± SD) at the initial event was 69 ± 9 and 72 ± 9 years at recurrence. Median interval between events was 18 months. Mean National Institutes of Health Stroke Scale (first/second event) was 4/9 at admission and 2/8 at discharge. Over 30% of patients developed symptomatic epilepsy. Etiologic distribution was (first/second event) the following: probable cerebral amyloid angiopathy (CAA) (12/20), possible CAA (3/0), hypertensive (5/4), anticoagulation (4/3), vascular malformation (2/4), ischemia with secondary hemorrhage (4/0), vasculitis (0/1), undetermined (4/0). Conclusions: Recurrent ICH is rare, CAA being its most common etiology. Etiology of ICH may differ between the first/second event in about 10%. The findings indicate the need of a complete and distinct work-up including MRI in every instance of ICH recurrence.